Analisis Kadar Karboksihemoglobin (COHb) dalam Darah Mahasiswa Perokok dan Bukan Perokok di Program Studi Teknologi Laboratorium Medis Universitas Mohammad Husni Thamrin - Ramadres, Gerab; Masdianto, Masdianto; Kristianingsih, Yuli; Sugiantari, Nining (Universitas Mohammad Husni Thamrin, 2025)
Smoking is a common behavior among adolescents. Consequently, it can affect the heart, central nervous system, and all oxygen-sensitive organs. This study aimed to determine differences in COHb levels in the blood of smokers and nonsmokers in the Medical Laboratory Technology Study Program at Universitas Mohammad Husni Thamrin. The Conway diffusion cell method, using sulfuric acid, was used to release carbon monoxide from hemoglobin molecules. UV-Vis spectrophotometry was used to identify single substances. COHb levels in 15 smokers were 0.53% and 0.26% in 15 nonsmokers. The study concluded that there were differences in COHb levels between smokers and nonsmokers. Both COHb levels were below the normal value of 3.5%, as determined by the Indonesian Minister of Health Regulation No. 70 of 2016. Keywords : Blood, COHb level, smoker